Effects of time after a second dose of immunization against GnRF (Improvest) independent of age at slaughter on commercial bacon slicing characteristics of immunologically castrated barrows. (January 2016) - Tavárez, M.A.; Bohrer, B.M.; Herrick, R.T.; Mellencamp, M.A.; Matulis, R.J.; Ellis, M.; Boler, D.D.; Dilger, A.C.
Abstract: The objective was to determine the effects of time after a second dose of anti-GnRF immunization on fresh belly characteristics and slicing yields of immunologically castrated (IC) barrows, physically castrated (PC) barrows and gilts slaughtered at 24 weeks of age. The second dose was staggered so that IC barrows were slaughtered at 4, 6, 8, or 10 weeks after the second dose. Fresh belly characteristics (N = 141) were collected at slaughter and bacon was manufactured commercially. The main effects in the model were treatment and the random effects of block and block within replication. Thickness, flop distance, and lipid content increased (L; P  < 0.04) and iodine value tended to decrease (L; P  = 0.08) with time after the second dose in IC barrows. Slicing yields increased with time after the second dose (L; P  < 0.01), but were similar ( P  = 0.11) among sexes. Increasing time of slaughter after second anti-GnRF dose improves fresh belly and bacon slicing characteristics in IC barrows. Highlights: Fresh belly characteristics improved as time of harvest after the second dose increased. Slice yield improved as time of harvest after the second dose increased. Bacon slicing yields did not differ among IC and PC barrows or gilts.